PREVALÊNCIA DA HIPERTENSÃO ARTERIAL SISTÊMICA E DIABETES MELLITUS ENTRE INDÍGENAS - Perla Katheleen Valente Corrêa; Fernanda Araújo Trindade; Camilla Cristina Lisboa do Nascimento; Aliny Cristiany Costa Araújo; Igor Kenji Yamamoto Souza; Laura Maria Vidal Nogueira (Universidade Federal do Paraná, 2021)
Objective: to analyze the prevalence of systemic hypertension and diabetes mellitus among indigenous villagers associated with ethnicity and describe the frequency of care/diagnosis according to professional category. Method: epidemiological and descriptive study, carried out with data on Systemic Hypertension and Diabetes Mellitus produced in the Distritos Sanitários Especiais Indígenas (Special Indigenous Health Districts of Pará), between 2013-2017, obtained from the Sistema de Informações da Atenção à Saúde Indígena (Indigenous Health Care Information System). For analysis, the morbidities were grouped, and Pearson's Chi-square was used, p≤0.05. Results: 624 cases of Systemic Arterial Hypertension and 108 cases of Diabetes mellitus were studied, identifying a greater involvement of women. The Munduruku ethnic group showed a higher prevalence of systemic hypertension (35.0%; n=219) and diabetes mellitus (23.1%; n=25). It was observed expressive participation of the nursing team in the care of indigenous peoples. Conclusion: The identified prevalence can be attributed to the accelerated nutritional transition and changes in lifestyle habits. Such findings are important for qualified and culturally meaningful nursing care.